2014
DOI: 10.3390/jfb5010001
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Uniquely-Processed Titanium on Biological Systems: Implications for Human Health and Performance

Abstract: Titanium is biocompatible and widely utilized in a variety of applications. Recently, titanium in pico-nanometer scale and soluble form (Aqua Titan) has expanded its use to applied human health and performance. The purpose of this article is to review the current evidence associated with specific physiological responses to Aqua Titan-treated materials. In vitro studies have shown that application of Aqua Titan can modify membrane potential and long-term potentiation in isolated hippocampal neurons, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
7
1
Order By: Relevance
“…Greater perfusion would suggest enhanced dilation of the arterioles feeding the associated capillary beds; but because of the trivial effect size, combined with the lack of microvascular blood flow or oxygen consumption changes, the physiological relevance of the effect remains to be confirmed. Our current findings therefore challenge the idea that enhanced musculoskeletal recovery arises via Aqua Titan-induced microvascular blood flow changes [ 29 ].…”
Section: Discussioncontrasting
confidence: 61%
“…Greater perfusion would suggest enhanced dilation of the arterioles feeding the associated capillary beds; but because of the trivial effect size, combined with the lack of microvascular blood flow or oxygen consumption changes, the physiological relevance of the effect remains to be confirmed. Our current findings therefore challenge the idea that enhanced musculoskeletal recovery arises via Aqua Titan-induced microvascular blood flow changes [ 29 ].…”
Section: Discussioncontrasting
confidence: 61%
“…Besides using RRM characteristic frequencies for bioactive peptide design or direct radiation with predicted electromagnetic wavelength producing desired biological and health effects, it is possible to use RRM identified frequencies to predict resonances between conductive elements like titanium salt and nanophotonic particles on one side with biological tissue also producing desired biological and health effects. It has been shown that titanium salt-infused patches with specific resonant characteristics are for example able to remediate pain, autism and attention deficit disorders when properly designed and applied [7,65,66]. The frequencies in such patches are produced with titanium salt-infused imprints and are passively transmitted through the skin contact.…”
Section: Titanium Salt Patches and Nanophotonic Particlesmentioning
confidence: 99%
“…In recent studies, it has been shown that the titanium in pico-nanometre scale and soluble form has beneficial effect on reduction of pain [66]. TERP patches are the silicon-based titanium salt-infused adhesive patches, which when directly applied to the pain areas, have been able to diminish pain, as shown in preliminary clinical studies [7].…”
Section: Titanium Salt Patches and Nanophotonic Particlesmentioning
confidence: 99%
“…One article shows that there are good effects for response of neuron, muscle, and psychological systems by in vitro, animals, and a few human studies, using the tape, wearing the necklace, or staying in the room containing titanium. 4 If such effects actually exist, some semipermanent change should be experienced by the patients with titanium implants in their bodies. However, in the present study and another, 5 there were no patients claiming postoperative improvements, casting doubt on the benefit of titanium in changing conditions.…”
Section: Discussionmentioning
confidence: 99%